Prognostic Factors of Success of Extracorporeal Shock Wave Lithotripsy 46 (ESWL) in The Treatment of Renal Stones. - Zaman, Md Masud; Rabby, Md Jamal E; Ali, Mohammad; Hassan, Md Kabirul; Rahman, Md Mustafizur; Ashaduzzaman, ATM (Journal of Surgical Sciences, 2019)
Background: Renal calculi are common approximately 50% of patient between the ages of 30and 50 years. The development of endourological and extracorporeal lithotripsy techniques ledto an increasing number of options for the management of renal calculi. Objective: To define factors those have a significant impact on the success rate after extracorporealshock wave lithotripsy (ESWL) for treatment of renal stones. Materials and Methods: Between April 2008 & December 2008, 64 patients with single ormultiple radiopaque renal stones (::s;30mm) were treated with ESWL monotherapy using StortzModulith SLX-F2 lithotriptor.The results of treatment were evaluated after 3 months of followupTreatment success was defined as complete clearance of the stones or presence ofclinically insignificant residual fragments (::s;4mm).The results of treatment were correlated withthe patient characteristics (age, sex, body mass index) and stone features (size, site, nature &radio density). Results: At 3-months follow-up, the overall success rate is 76%. Among them, repeated ESWLsessions are required in 19 patients (53.9%). Post-ESWL complications are recorded in 8patients (12.5%). Using the x2 test, only three factors have a significant impact on the successrate, namely: stone site, size (the largest diameter of the stone), stone number & BMI (BodyMass Index). The success rate is highest for stones located in the upper calyx (15/15; 100%)and lowest for those located in the lower calyx (10/16; 62.5%) (p=.005). Stones with a largestdiameter ot s 15mm are associated with a success rate of 90.2% (37 /41), compared to 52.2%(12/23) for those with a diameter of >15mm (p=.001). The success rate is also higher forsingle stone (46/56; 82%) than multiple stones (3/8; 37.5%) (p=0.005).Patients with lowerBMI (<24) have a better success than higher BMI (>25) (p=0.01) Conclusion: The success rate of ESWL for the treatment of renal stones can be predicted bystone size, location, number and patient BMI. Journal of Surgical Sciences (2016) Vol. 20 (2) :46-50